Response of broilers subjected to an enteric challenge and fed diets with varying limestone particle sizes and calcium concentrations–part 1: performance, tibia mineralization, and nutrient digestibility - J.P. Gulizia; R.W. Tabish; J.I. Vargas; J.R. Hernandez; C.T. Simões; E.G. Guzman; S.J. Rochell; R. Hauck; M.A. Bailey; W.A. Dozier; K.W. McCafferty; W.J. Pacheco (Poultry Science)
This 35-d experiment evaluated the effects of limestone particle size and calcium concentrations on broiler performance, tibia mineralization, and nutrient digestibility. Two thousand one hundred d-old YPM x 708 male broilers were distributed into 70 floor pens and assigned to 1 of 7 treatments (10 replicates/treatment). This experiment was a 2 × 3 + 1 factorial arrangement, including 2 limestone particle sizes (910 and 200 µm) and 3 calcium concentrations (adequate, reduced, and low), and an unchallenged control. Dietary calcium was reduced in two 0.10 percentage unit steps from adequate concentrations (i.e., breeder recommendations). All factorial treatments were enterically challenged with Eimeria spp. and Clostridium perfringens. Performance (d 17, 21, 26, and 35), tibia mineralization (d 21 and 35), and nutrient and energy digestibility (d 21 and 35) were measured. The enteric challenge reduced BW and increased feed conversion ratios (FCR; contrast, P ≤ 0.05). Broilers fed adequate and reduced calcium diets had higher BW, tibia shear strength, and tibia ash on d 35 compared to low calcium diets (main effect, P ≤ 0.05). Day 1 to 35 FCR linearly increased as dietary calcium decreased from adequate to low in the group fed 910 µm limestone, whereas in the 200 µm limestone group, only the low calcium and not the reduced calcium led to higher FCR compared with those fed adequate calcium (interaction, P ≤ 0.05). Broilers fed reduced and low calcium diets with 910 µm limestone had the highest calcium and phosphorus digestibility on d 21. With 200 µm limestone, broilers fed a low calcium diet had higher mineral digestibility (interaction, P ≤ 0.05). Day 35 apparent ileal digestible energy (AIDE) increased when broilers consumed an adequate or reduced calcium diet compared to low calcium (main effect, P ≤ 0.05). This experiment demonstrated dietary calcium concentrations 0.10 percentage units lower than recommended concentrations can maintain broiler performance, tibia mineralization, and AIDE during an enteric challenge. However, calcium concentration effects depended on limestone particle size.